Developing Cultural Reserve Awareness for Guppi Samata Islamic Boarding School Students in Gowa District (Based on Asset Potential) - Syukur, Syamzan; Syakur, Nur Aksan; Idris, Muhammad; Muh. Kaswin, (Al-Hikmah, 2024)
Cultural Heritage is one of the legacies left by ancestors in the form of objects or buildings that hold significant value for history, culture, and science. The Cultural Heritage Law No. 11 of 2010 provides protection for cultural heritage sites. However, there are still instances of large-scale and intentional exploitation or destruction of some cultural heritage sites. Therefore, strategic steps are needed for their preservation, including involving various community layers in preserving cultural heritage. Several approaches in preserving cultural heritage include raising awareness among students at Guppi Islamic Boarding School, who represent the millennial community or young generation. This approach also offers an opportunity for various community layers to become crucial agents in cultural heritage preservation. The methods used for raising awareness at Guppi Islamic Boarding School are: 1) Asset-Based Community Development (ABCD); this approach emphasizes utilizing the assets of the assisted community (students of Guppi Islamic Boarding School). Generally, this community has a close affinity with science and technology and tends to have high curiosity, which can be managed effectively. 2) Community-Based Research (CBR); this research model involves the target community as active participants. The awareness-building model at Guppi Islamic Boarding School includes two stages: theoretical stage through briefing and socialization of Law No. 11 of 2010 and practical stage, such as heritage tourism. The awareness-building activities benefit the institution and the assisted community, particularly in increasing knowledge and building awareness among Guppi Islamic Boarding School students.